MCSS: microbial community simulator based on structure - Hui, Xingqi; Yang, Jinbao; Sun, Jinhuan; Liu, Fang; Pan, Weihua (Frontiers in Microbiology, 2024)
De novo assembly plays a pivotal role in metagenomic analysis, and the incorporation of thirdgeneration sequencing technology can significantly improve the integrity and accuracy of assembly results. Recently, with advancements in sequencing technology (Hi-Fi, ultra-long), several long-readbased bioinformatic tools have been developed. However, the validation of the performance and reliability of these tools is a crucial concern. To address this gap, we present MCSS (Microbial Community Simulator based on Structure), which has the capability to generate simulated microbial community and sequencing datasets based on the structure attributes of real microbiome communities. The evaluation results indicate that it can generate simulated communities that exhibit both diversity and similarity to actual community structures. Additionally, MCSS generates synthetic PacBio HiFi and Oxford Nanopore Technologies (ONT) long reads for the species within the simulated community. This innovative tool provides a valuable resource for benchmarking and refining metagenomic analysis methods.